2018
DOI: 10.2147/vhrm.s158641
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence to statins: individualized intervention strategies outside the pill box

Abstract: Poor adherence to statin therapy is linked to significantly increased risk of cardiovascular events and death. Unfortunately, adherence to statins is far from optimal. This is an alarming concern for patients prescribed potentially life-saving cholesterol-lowering medication, especially for those at high risk of cardiovascular events. Research on statin adherence has only recently garnered broader attention; hence, major reasons unique to adherence to statin therapy need to be identified as well as suggestions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 91 publications
1
36
0
1
Order By: Relevance
“…[1][2][3][4] However, adherence to statin therapy is extremely poor in clinical practice. [5][6][7][8] Medication non-adherence usually refers to whether patients fail to take the medication as directed (dose and frequency of regimen) and/or discontinue it prematurely [9]. It is a growing concern to clinicians, healthcare systems, and other stakeholders, [10] because of its high prevalence and its association with adverse outcomes and higher costs of care.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, adherence to statin therapy is extremely poor in clinical practice. [5][6][7][8] Medication non-adherence usually refers to whether patients fail to take the medication as directed (dose and frequency of regimen) and/or discontinue it prematurely [9]. It is a growing concern to clinicians, healthcare systems, and other stakeholders, [10] because of its high prevalence and its association with adverse outcomes and higher costs of care.…”
Section: Introductionmentioning
confidence: 99%
“…14 Previous studies on adherence to statin treatment showed that in longer periods of time (6 months), around 50-60% patients continue on treatment. 15,16 Treatment adherence was not considered in the present study, but we previously reported that one out of four patients (25%) stated to have forgotten at least one dose of their treatment, regardless of disease and duration of treatment. 17 Although the retrospective design of the study and the lack of a stratified sampling constitute limitations to the analysis of the results, we conclude that there is a very low rate of ATP III therapy goal achievement among patients with dyslipidemia categorized as high and very high cardiovascular risk, independently of the treatment option or its duration.…”
Section: Discussionmentioning
confidence: 89%
“…Several authors have presented evidence that the knowledge of pharmacotherapy is associated with compliance, and consequently, there is a higher change of therapeutic success. (31)(32)(33)(34)(35) No studies were found evaluating the level of knowledge of the Brazilian population about the drugs. In this case, we point out the importance of performing nationwide studies that evaluate the knowledge of the population about pharmacotherapy, in order to direct strategies and public policies, with a view to therapeutic success.…”
Section: ❚ Resultsmentioning
confidence: 99%